Synthesis of new asymmetrical frame phosphonates based on Sesamol - Zalaltdinova, A.; Appazov, N.; Sadykova, Yu.; Gazizov, A.; Burilov, A. (Edelweiss Applied Science and Technology, 2025)
A method for synthesizing new asymmetrical frame phosphonates is proposed, based on the reaction of dichlorophosphonate with an equimolar mixture of two different phenols in toluene, in the presence of trifluoroacetic acid. The reaction of sesamol with resorcinol (or 2-methylresorcinol or pyrogallol) and 2-ethoxyvinyl dichlorophosphonate yielded an unexpected result—a crystalline product with good solubility in dimethyl sulfoxide, representing an inseparable mixture of asymmetrical and symmetrical frame phosphonates based on sesamol. Due to their similar chromatographic mobility, it was not possible to isolate the individual compounds. A similar outcome was observed when 2-ethoxyvinyl dichlorophosphonate reacted with a mixture of sesamol and 2,4-dimethylresorcinol: a mixture of symmetrical and asymmetrical frame phosphonates was formed, with the symmetrical product derived from 2,4-dimethylresorcinol. This synthetic outcome can be explained by the higher reactivity of 2,4-dimethylresorcinol compared to sesamol. Ultimately, in both reactions, the symmetrical frame phosphonate based on sesamol was formed and subsequently isolated in its pure form. The validity of the obtained results is supported by modern physicochemical analytical methods, including mass spectrometry (MALDI-TOF), IR spectroscopy, ¹H, ¹³C, and ³¹P NMR spectroscopy, elemental analysis, and X-ray crystallography.